Up-to-date earthquake and focal mechanism solutions datasets for the assessment of seismic hazard in the vicinity of the United Arab Emirates - Sawires, Rashad; Peláez, José A; AlHamaydeh, Mohammad; Henares, Jesús (Data in Brief, 2020)
This article presents updated and unified Poissonian earthquake and focal mechanism catalogs for the United Arab Emirates and its surroundings. Data were compiled from different local, regional, and international sources. Several magnitude-conversion relationships have been applied to obtain the unified moment magnitude estimates for the final datasets. Dependent earthquakes were identified and removed from the compiled data via a declustering process to ensure a time independent Poissonian distribution of seismicity. The final compiled earthquake catalog is comprised of 1464 mainshocks, which span the time period of 658–2019 [1]. The range of their spatial region is 21°–31°N on the latitude and 47° to 66°E on the longitude. Additionally, an overall number of 583 focal mechanism solutions spanning the time period of 1923–2015 were acquired [1]. Such datasets are compatible with other published catalogs from across the globe which provide a basis for the estimation of seismic hazard and risk, as well as, the establishment of a unified seismic action representation in the building codes for the United Arab Emirates. This paper and its dataset are a companion for a published article in the Journal of Asian Earth Sciences under the title “A State-Of-The-Art Seismic Source Model for the United Arab Emirates” [2].
Keywords: earthquake catalog; focal mechanism solutions; moment magnitude; seismic hazard; United Arab Emirates; Scopus; Emerging